Can we rely on forest reserves for primate conservation?. (17th July 2015) - Mugume, Sam; Chapman, Colin A.; Isabirye‐Basuta, Gilbert; Otali, Emily
Abstract: Tropical forests contain much of the world's biodiversity, yet their rate of decline is increasing. The strategy most frequently used to protect this biodiversity is to make parks and reserves. While there is a great deal of research on the effectiveness of parks for protecting biodiversity, there is little research on how well extractive reserves conserve biodiversity. Here, we evaluate the effectiveness of four forest reserves in western Uganda at maintaining populations of primates and compare census data from the reserves to data from the neighbouring well‐protected Kibale National Park. The relative abundance of the five most common primates in the park was approximately four times that of the forest reserves. In the forest reserves, evidence of new human encroachment was seen every 500 m, while in the park it was seen every 100, 000 m. Two recommendations emerge from our research: (i) for forest reserves, such as those studied here, to have conservation value for primates, extraction must be reduced and (ii) until the long‐term viability of the populations in forest reserves can be ascertained, they should not be considered in estimates of the sizes of endangered species protected ranges.